Safely resuming neglected tropical disease control activities during COVID-19: Perspectives from Nigeria and Guinea - McKay, Stephanie; Shu’aibu, Joy; Cissé, Abdourahim; Knight, Albi; Abdullahi, Fadhalu; Ibrahim, Ahmed; Madaki, Suzie; Genovezos, Chantelle; McCoy, Kate; Downs, Philip; Kabore, Achille; Adamu, Helen; et al. (PLOS Neglected Tropical Diseases, 2021)
Since its early spread in early 2020, the disease caused by the novel Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Coronavirus Disease 2019 (COVID-19) has caused mass disruptions to health services. These have included interruptions to programs that aimed to prevent, control, and eliminate neglected tropical diseases (NTDs). In March 2020, the World Health Organization (WHO) released interim guidelines recommending the temporary cessation of mass drug administration (MDA), community-based surveys, and case detection, while encouraging continuation of morbidity management and vector control where possible. Over the course of the following months, national programs and implementing partners contributed to COVID-19 response efforts, while also beginning to plan for resumption of NTD control activities. To understand the challenges, opportunities, and recommendations for maximizing continuity of disease control during public health emergencies, we sought perspectives from Nigeria and Guinea on the process of restarting NTD control efforts during the COVID-19 pandemic. Through semistructured interviews with individuals involved with NTD control at the local and national levels, we identified key themes and common perspectives between the 2 countries, as well as observations that were specific to each. Overall, interviewees stressed the challenges posed by COVID-19 interruptions, particularly with respect to delays to activities and related knock-on impacts, such as drug expiry and prolonged elimination timelines, as well as concerns related to funding. However, respondents in both countries also highlighted the benefits of a formal risk assessment approach, particularly in terms of encouraging information sharing and increasing coordination and advocacy. Recommendations included ensuring greater availability of historical data to allow better monitoring of how future emergencies affect NTD control progress; continuing to use risk assessment approaches in the future; and identifying mechanisms for sharing lessons learned and innovations between countries as a means of advancing postpandemic health systems and disease control capacity strengthening.